High-Gain Microstrip Patch Antenna Array Using Artificial Magnetic Conductor Structures: Array Antena Patch Mikrostrip Gain Tinggi Menggunakan Struktur Konduktor Magnetik Buatan 4o - Saba F. Ahmed Jaf; Amenah Edrees Kanaan (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Microstrip patch antennas (MSPAs) are widely applied in wireless communication due to their compactness, low cost, and ease of fabrication. Specific background: Recent technological advancements have focused on enhancing MSPA performance for applications in Wi-Fi, radar, and medical implantable devices. Knowledge gap: However, optimizing antenna gain while minimizing return loss across varied array configurations and frequencies remains insufficiently explored. Aims: This study aims to design and analyze 1, 2×2, 3×3, and 4×4 MSPA arrays operating at 10 GHz and 13 GHz using the HFSS simulator, comparing their return loss and gain performance. Results: The optimized 4×4 MSPA array demonstrated a maximum gain of 14.5 dBi with a 17% radiation efficiency improvement and reduced back-lobe radiation, outperforming conventional designs. Novelty: Incorporation of artificial magnetic conductor (AMC) units into the array structure significantly enhanced gain, directivity, and front-to-back ratio while maintaining a low-profile configuration, simplifying fabrication. Implications: These findings provide a systematic approach to optimizing MSPA arrays, offering practical benefits for applications in next-generation wireless systems, radar technologies, and biomedical devices. Highlights: Optimized Design: AMC boosts gain and minimizes return loss. Broad Application: Supports Wi-Fi, radar, and medical devices. Easy Fabrication: Low-profile antenna simplifies manufacturing process. Keywords: Microstrip Patch Antenna, HFSS Simulation, Antenna Array, Artificial Magnetic Conductor, Gain Enhancement